Islam-Buddhism Eco Dialogue (IBED): application of religion and science to ecology and sustainability - Bakar, Osman (Muslim Youth Movement of Malaysia (ABIM), Vajrayana Buddhist Council of Malaysia (VBCM), Tibetan Buddhist Culture Centre of Malaysia (TBCC), Centre for Civilisational Dialogue (UMCCD), UM, 2023)
Religion has major roles to play in addressing climate change and the socio-economic sustainability crisis that goes with it and such roles have been empirically verified. The crucial role of religion in issues concerning climate catastrophes and climate justice for example, rests basically on its ethical teachings, reach and influence, and ability to inspire adherents to action. These significant religious and spiritual influences on the ethical dimension of the climate crisis also point to a greater potential for the future role of religion in providing solutions to ecological problems. Based on their ecological, scientific, as well as theological knowledge and experiences, the contributors of the book gave clear testimony to these findings.